1997
DOI: 10.1073/pnas.94.25.13955
|View full text |Cite
|
Sign up to set email alerts
|

A dichotomous role for nitric oxide during acuteToxoplasma gondiiinfection in mice

Abstract: Production of nitric oxide by macrophages is believed to be an important microbicidal mechanism for a variety of intracellular pathogens, including Toxoplasma gondii. Mice with a targeted disruption of the inducible nitric oxide synthase gene (iNOS) were infected orally with T. gondii tissue cysts. Time to death was prolonged compared with parental controls. Histologic analysis of tissue from infected mice showed scattered small foci of inf lammation with parasites in various tissues of iNOS؊͞؊ mice, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
149
3
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(172 citation statements)
references
References 31 publications
16
149
3
4
Order By: Relevance
“…The detection of bacteria in inflamed subepithelial tissue layers by FISH demonstrated that T. gondii-induced ileal inflammation is accompanied by substantial mucosal barrier defects resulting in bacterial translocation. The finding that live E. coli, but not Bacteroides/Prevotella spp., were detected by culture in Ͼ80% of the mesenteric lymph nodes and in 70% of the spleens from mice with severe ileitis (data not shown) suggests that following translocation gut bacteria potentiate tissue destruction and intestinal inflammation by direct cell contact and mediator release (33,68). Such interactions are further supported by decreased IFN-␥ and NO levels after antibiotic treatment and by the elevated intestinal NO levels in gnotobiotic animals monocolonized with E. coli.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The detection of bacteria in inflamed subepithelial tissue layers by FISH demonstrated that T. gondii-induced ileal inflammation is accompanied by substantial mucosal barrier defects resulting in bacterial translocation. The finding that live E. coli, but not Bacteroides/Prevotella spp., were detected by culture in Ͼ80% of the mesenteric lymph nodes and in 70% of the spleens from mice with severe ileitis (data not shown) suggests that following translocation gut bacteria potentiate tissue destruction and intestinal inflammation by direct cell contact and mediator release (33,68). Such interactions are further supported by decreased IFN-␥ and NO levels after antibiotic treatment and by the elevated intestinal NO levels in gnotobiotic animals monocolonized with E. coli.…”
Section: Discussionsupporting
confidence: 58%
“…Within 8 days after peroral infection with Toxoplasma gondii, susceptible C57BL/6 mice develop severe ileal inflammation, resulting in necroses of mucosal villi and complete tissue destruction (32,33). Ileitis is caused by a Th1-type immunopathology, characterized by a CD4 ϩ T cell-mediated increase in proinflammatory mediators including IFN-␥, TNF-␣, and NO.…”
Section: Gram-negative Bacteria Aggravate Murine Small Intestinal Th1mentioning
confidence: 99%
“…Sections of small bowel and liver from infected parental mice showed the patchy epithelial necrosis and scattered hepatic inflammatory nodules ( Fig. 2 A and B) typical of the hyperimmune response to T. gondii infection (11,26). IL-15 Ϫ/Ϫ mice showed similar changes, with perhaps more inflammation than the controls, but the affected segments of bowel were minimal and most gut epithelia were intact (Fig.…”
Section: Il-15mentioning
confidence: 66%
“…In response to the infection, LP CD4 + T lymphocytes secrete INF-+ and TNF- § , which are microbicidal compounds and are associated with the induction of iNOS and subsequent expression of NO [19]. Although essential for limiting parasite invasiveness, the overproduction of these molecules is disruptive to normal intestinal homeostasis [20]. The decreased production of IFN-+ and TNF- § observed after the adoptive transfer of P IEL would then result in decreased inflammation and an increase in the survival of the recipient mice.…”
Section: Discussionmentioning
confidence: 99%